An Investigation of Pre-Service and In-Service Teachers’ Perceptions of Teacher Quality in Turkey - Görsev Sönmez Boran; Nuri Can Aksoy; Burcu Gürkan (Sakarya University Journal of Education)
Present studyinvestigates the senior-level Turkish pre-service and in-service teachers’perceptions of teacher quality with a descriptive survey method. Data for thisstudy were gathered through Teacher Quality Survey (TQS) and open-endedquestions from 210 pre-service teachers enrolled in four different universitiesin Turkey and 147 in-service teachers from different majors. Results of thestudy showed that both pre-service and in-service teachers think that teachers’relationship with the students affect students’ success and teachers shouldtake the individual differences into consideration. Moreover, according to thepre-service teachers, teachers should know how to teach and assess what theyteach, and they need to know time management. On the other hand, in-service teachersconsider that teachers should follow current developments, should have theresearcher identity and should understand students’ needs and interests.Present study also suggested both academic and practical implications